Examination of Early Functional Recovery After ACL Reconstruction: Functional Milestone Achievement and Self-Reported Function. (July 2018) - Obermeier, Michael C.; Sikka, Robby S.; Tompkins, Marc; Nelson, Bradley J.; Hamilton, Abigail; Reams, Megan; Chmielewski, Terese L.
Background: Few studies have documented early functional recovery after anterior cruciate ligament (ACL) reconstruction. Purpose: To quantify the time to early functional milestone achievement and change in function over 12 weeks after ACL reconstruction and to identify demographic characteristic predictors of the outcomes. Study Design: Prospective, longitudinal, observational study. Level of Evidence: Level 4. Methods: A total of 182 patients (95 females, 87 males; mean ± SD age, 28 ± 12 years; mean ± SD body mass index [BMI], 25 ± 4 kg/m 2 ) who received primary, unilateral, ACL reconstruction were included. Testing occurred before surgery as well as 1, 2, 4, 8, and 12 weeks postsurgery. Outcomes included demographic characteristics, self-reported functional milestone achievements and responses on the Short Musculoskeletal Function Assessment (SMFA) questionnaire. Time to functional milestone achievement was calculated, and patients were categorized into "faster" or "prolonged" recovery groups based on the median value. Longitudinal change in SMFA subscale scores (daily activities and mobility) as well as demographic predictors of functional recovery group assignment and postsurgical change in SMFA subscale scores were examined. Results: Median time for discontinuing narcotic pain medication was 9 days, while that for discontinuing crutches was 15 days. Time to return to work occurred at a median of 11 days, return to school at 7 days, and return to driving at 11 days. Both SMFA subscale scores significantly decreased (improved) over time, with the greatest change occurring between 1 and 4 weeks postsurgery. The demographic predictor of faster functional recovery for discontinuation of narcotic pain medication was surgery with allograft; those for return to work were higher age, male sex, decreasing BMI, and sedentary/light occupational demand; and those for return to driving were higher age, male sex, and surgery on the left side of the body. Conclusion: Functional recovery occurs rapidly over the first month after ACL reconstruction for most patients. Nonmodifiable demographic characteristics may influence recovery time for specific functional milestones. Clinical Relevance: Results can be used to counsel patients on early functional recovery after ACL reconstruction.